Matrix Density Drives 3D Organotypic Lymphatic Vessel Activation in a Microfluidic Model of the Breast Tumor Microenvironment - Lugo-Cintrón, Karina M. (Lab Chip, 2020)
Lymphatic vessels (LVs) have been suggested as a preferential conduit for metastatic progression in breast cancer, where a correlation between the occurrence of lymph node metastasis and an increased extracellular matrix (ECM) density has been reported. However, the effect of ECM density on LV function is largely unknown. To better understand these effects, we used a microfluidic device to recreate tubular LVs in a collagen type I matrix. The density of the matrix was tailored to mimic normal breast tissue using a low-density collagen (LD-3 mg/mL) and cancerous breast tissue using a high-density collagen (HD-6 mg/mL). We investigated the effect of ECM density on LV morphology, growth, cytokine secretion, and barrier function. LVs cultured in HD matrices showed morphological changes as compared to LVs cultured in a LD matrix. Specifically, LVs cultured in HD matrices had a 3-fold higher secretion of the pro-inflammatory cytokine, IL-6, and a leakier phenotype, suggesting LVs acquired characteristics of activated vessels. Interestingly, LV leakiness was mitigated by blocking the IL-6 receptor on the lymphatic ECs, maintaining endothelium permeability at similar levels of LV cultured in a LD matrix. To recreate a more in vivo microenvironment, we incorporated metastatic breast cancer cells (MDA-MB-231) into the LD and HD matrices. For HD matrices, co-culture with MDA-MB-231 cells exacerbated vessel leakiness and secretion of IL-6. In summary, our data suggest that (1) ECM density is an important microenvironmental cue that affects LV function in the breast tumor microenvironment (TME), (2) dense matrices condition LVs towards an activated phenotype and (3) blockade of IL-6 signaling may be a potential therapeutic target to mitigate LV dysfunction. Overall, modeling LVs and their interactions with the TME can help identify novel therapeutic targets and, in turn, advance therapeutic discovery.